Grains of Sand and an Artist's Hands - Angela Peterman Mihalic (University Library System, University of Pittsburgh, 2015)
Shelly is a unique individual who has an extraordinary gift for the arts in all forms, along with a deep understanding of the human condition and how disease impacts individuals, families, and society at large. She has the ability to combine her artistic gifts with her love of science to make a powerful and significant impact on health.